2015
DOI: 10.1177/0042085915618710
|View full text |Cite
|
Sign up to set email alerts
|

AYP Status, Urbanicity, and Sector: School-to-School Variation in Instruction

Abstract: This study investigates whether adequate yearly progress (AYP) status, locale, and sector-common variables used to judge the quality of schoolsaccurately signal true differences in instructional practices in high school mathematics and science. Using data from the High School Longitudinal Study (HSLS), we find the school-to-school variation in instructional practices to be minimal. Controlling for a variety of school and teacher characteristics, we find that there is no difference in the use of developmental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although only 6% of the teacher-level variance occurred at the school level, he did find sector differences in use of student-centered teaching practices. Similarly, Northrop and Kelly (2018) found limited variation in developmental instruction in math and science between schools, ICCs of .084 and .110, respectively, in the High School Longitudinal Study data.…”
Section: Prior Research On School-to-school Variation In Instruction: Limited Evidence From Survey Reportsmentioning
confidence: 91%
“…Although only 6% of the teacher-level variance occurred at the school level, he did find sector differences in use of student-centered teaching practices. Similarly, Northrop and Kelly (2018) found limited variation in developmental instruction in math and science between schools, ICCs of .084 and .110, respectively, in the High School Longitudinal Study data.…”
Section: Prior Research On School-to-school Variation In Instruction: Limited Evidence From Survey Reportsmentioning
confidence: 91%
“…More basically, the concept of opportunity to learn helps explain school-to-school differences in achievement growth (Montt 2011;Martin 2009). Within this framework, dimensions of schooling that affect learning include teacher characteristics and instructional quality (e.g., Kelly 2010;Kelly and Majerus 2011;Northrop and Kelly 2018;Minor et al 2015); the degree of exposure to rigorous educational content (e.g., Hansen and Strietholt 2018;Northrop et al 2019); and even basic physical resources and availability of learning materials and technology (e.g., Krashen et al 2012).…”
Section: High School Stem Learning: An Opportunity To Learn Perspectivementioning
confidence: 99%
“…Carbonaro and Covay (2010) suggested that this result might be related to the difference in academic curriculum between private and public schools. Private schools follow a rigorous curriculum, so urban schools may need to enhance the quality of the instruction to improve the learning gains through utilizing innovative and research-based strategies (Northrop & Kelly, 2018). These results call for further examination of the quality of the instruction and factors influencing the instruction in different schools and in different grade levels including elementary, middle, high school and college education through longitudinal studies.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…Moreover, school-level factors can be related to the students' achievement (e.g. Carbonaro & Covay, 2010;Northrop & Kelly, 2018;Perry & McConney, 2010). These previous studies investigated the influence of these individual-level and school-level factors on student achievement separately.…”
Section: Introductionmentioning
confidence: 99%